Positive Predictions of International Institutions, Demographic Bonuses and Covid-19: Will Indonesia Really Enjoy the Demographic Bonus Amid the Raging Covid-19 Pandemic? - Endro Tri Susdarwono (Future Science, 2022)
This study aims to provide a description of the positive predictions of international institutions, demographic bonuses and covid-19: will Indonesia really enjoy the demographic bonus in the midst of the Covid-19 pandemic? This study uses a qualitative method that uses a type of literature study which is carried out by examining several theories that depart from a problem then analyzed from various literatures ranging from available journals, the internet, and various existing facts. The data collection method used is through data reduction techniques, namely the selection, simplification, and transportation of data so that results or conclusions are drawn up systematically. This study concludes that the experiences of South Korea, China, and the United States are very different from Indonesia, these countries can enjoy a demographic bonus without any barrier variables in the form of the Covid-19 pandemic. Meanwhile, the demographic bonus with the growth of baby boomers in the Golden Indonesia era was obtained by this extraordinary event. Both indicators and parameters will of course differ from these countries. So this is a very big gamble for Indonesia to be in accordance with what has been predicted by the international institutions or vice versa.